Analisis Strategi Manajemen Kesehatan di Rumah Sakit Dalam Memaksimalkan Mutu Pelayanan Kesehatan: Literature Review - Alya Indana Zulfa; Dinda Febriani; Anggi Fadillah Putri Siregar; Dewi Agustina (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
Based on the Regulation of the Minister of Health of the Republic of Indonesia No. 72 of 2016, a hospital is an individual health service facility that provides inpatient and outpatient care, therefore quality services must be fulfilled by the hospital. To maximize service to patients, the operational system must be made more effective. and also efficient. The quality of health services is very important to the quality of health. Improving the quality of health services also requires a strategy in order to maintain or the level of performance of health services. This study uses a literature review study approach using several selected sources based on the criteria of a range of years and keywords that have been determined by the researcher that strategic management in an efficient operation will provide optimal service to patients. Thus, it will give a positive response in the form of patient satisfaction.